Sedentary employees and their attitude to sport - Juříková, Jana (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
This study has used the questionnaire method to find out whether and to which extent persons engaged in sedentary employment, devote their leisure time to physical activities. Respondents were 70 employees working in the office. Examination of anthropometric parameters revealed that 45.6% of the respondents is overweight or obese, some persons confirmed overweight or obesity occurrence in the family history and in other family members. Merely 40% of respondents were satisfied with their bodies. However, in their leisure time, most respondents perform sports activity only occasionally or not at all.